Sevoflurane Aggravates the Progress of Alzheimer’s Disease Through NLRP3/Caspase-1/Gasdermin D Pathway - Tian, Di; Xing, Yanmei; Gao, Wenli; Zhang, Hongyan; Song, Yifeng; Tian, Ya; Dai, Zhongliang (Frontiers in Cell and Developmental Biology, 2022)
Background: Alzheimer’s disease (AD) is the most common form of dementia worldwide. Previous studies have reported that sevoflurane, a frequently used anaesthetic, can induce cognitive impairment in preclinical and clinical settings. However, the mechanism underlying the development of this neurotoxicity is currently unclear. Methods: Seven-month-old APP/PS1 mice were placed in an anaesthesia induction box containing 3% sevoflurane in 100% O2 for 6 h, while BV2 cells were cultured with 4% sevoflurane for 6 h. Pyroptosis and tau protein expression in excised hippocampus tissues and cells were measured using western blotting and immunofluorescence assay. Caspase-1 and NLRP3 were knocked out in BV2 microglia using CRISPR/Cas9 technology to determine whether they mediate the effects induced by sevoflurane. Results: Sevoflurane directly activated caspase-1 to induce pyroptosis in the mouse model of AD via NLRP3 and AIM2 activation. In addition, sevoflurane mediated cleavage of gasdermin D (GSDMD) but not GSDME, promoted the biosynthesis of downstream interleukin-1β and interleukin-18, and increased β-amyloid (Aβ) deposition and tau phosphorylation. The nontoxic caspase-1 small molecule inhibitor VX-765 significantly inhibited this activation process in microglia, while NLRP3 deletion suppressed sevoflurane-induced caspase-1 cleavage and subsequently pyroptosis, as well as tau pathology. Furthermore, silencing caspase-1 alleviated the sevoflurane-induced release of IL-1β and IL-18 and inhibited tau-related enzymes in microglia. Conclusions: This study is the first to report that clinical doses of sevoflurane aggravate the progression of AD via the NLRP3/caspase-1/GSDMD axis. Collectively, our findings elucidate the crucial mechanisms of NLRP3/caspase-1 in pyroptosis and tau pathogenesis induced by sevoflurane and suggests that VX-765 could represent a novel therapeutic intervention for treating AD.